2020
DOI: 10.1111/1440-1681.13231
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA‐148b‐3p alleviates oxygen‐glucose deprivation/reoxygenation‐induced apoptosis and oxidative stress in HT22 hippocampal neuron via reinforcing Sestrin2/Nrf2 signalling

Abstract: MicroRNAs (miRNAs) have emerged as crucial regulators of neuronal injury during cerebral ischaemia/reperfusion injury. Various miRNAs are dysregulated during this pathological process; however, the precise role of these miRNAs in regulating neuronal injury remains largely unknown. In the current study, we explored the potential function of microRNA‐148b‐3p (miR‐148b‐3p) in regulating neuronal injury induced by oxygen‐glucose deprivation/reoxygenation (OGD/R) in vitro, a cellular model for mimicking cerebral is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Mitogen-activated protein kinase (MAPK) (Liu et al , 2019a, Ola-Davies et al , 2019 and mammalian target of rapamycin (mTOR) (Qiao et al , 2019, Yuan et al , 2019 can act as upstream mediators of the Nrf2 signaling pathway. Based on these studies, we can conclude that Nrf2 pathway may be a down-stream mediator of the miRs (Chi et al , 2019, Du et al , 2019, Qin et al , 2019, Wu et al , 2019a.…”
Section: Genetic Regulationmentioning
confidence: 88%
“…Mitogen-activated protein kinase (MAPK) (Liu et al , 2019a, Ola-Davies et al , 2019 and mammalian target of rapamycin (mTOR) (Qiao et al , 2019, Yuan et al , 2019 can act as upstream mediators of the Nrf2 signaling pathway. Based on these studies, we can conclude that Nrf2 pathway may be a down-stream mediator of the miRs (Chi et al , 2019, Du et al , 2019, Qin et al , 2019, Wu et al , 2019a.…”
Section: Genetic Regulationmentioning
confidence: 88%
“…24 Moreover, the up-regulation of SESN2 protects neurons from oxygen-glucose deprivation/re-oxygenation-induced apoptosis and oxidative stress in vitro . 15,25 These studies suggest a considerable neuroprotective function of SESN2. Consistently, in this study, we found that SESN2 expression was induced in cortical neurons injured by scratch, an in vitro model of TBI.…”
Section: Discussionmentioning
confidence: 90%
“…SESN2 is closely associated with these processes, especially oxygen free radical damage. A study by Du et al 85 demonstrated that SESN2 alleviated oxygen‐glucose deprivation and reoxygenation‐induced apoptosis via the NRF2 pathway. Besides, SESN2 overexpression markedly decreased cerebral I/R injury by upregulating NRF2 in the nucleus 86 .…”
Section: Sestin2 and Diseasesmentioning
confidence: 99%